FINANCIAL LITERACY FOR FINANCIAL RESILIENCE AMONG GIG WORKERS OF THE RIDE-HAILING SERVICE SECTOR IN SUBANG - Estu Widarwati; Carissa Salsabila; E Wityasminingsih (STIESA-PRESS, 2025)
The growth of the gig economy has created a new category of workers with income that is often unstable, raising questions about their ability to manage finances and withstand economic shocks. This study aims to analyze the financial literacy for financial resilience among ride-hailing gig workers in Subang Regency. This study investigates the impact of financial literacy on financial resilience among university students in Subang, West Java. The literacy activity was conducted in September 2025 with 50 randomly selected gig workers of the ride-hailing service sector in Subang. The stages of implementing activities include distributing structured questionnaires and evaluating feedback using quantitative, descriptive, and exploratory approaches. Using a quantitative approach, data were collected through questionnaires distributed to students. Findings indicate that he results show that gig workers in Subang have a very good level of financial literacy (87.7%) and financial resilience (87.5%), with the strongest aspects found in debt control and long-term financial planning, while knowledge of interest rates and income stability remain relatively weak. There is strong evidence of financial literacy on financial resilience. The findings highlight the importance of financial literacy in strengthening financial resilience, while also suggesting that other factors such as income, working hours, and social support are influential.